Confirmation of MB-type monoclinic phase in Pb[(Mg1/3Nb2/3)0.71Ti0.29]O3: A powder neutron diffraction study - Singh K.; Pandey D.; Zaharko O. (My University, 2025)
Analysis of high-resolution powder neutron diffraction data for Pb[(Mg1/3Nb2/3)0.71Ti0.29]O3 is presented to show unambiguously that its structure is not rhombohedral but monoclinic of MB type. Presence of this phase in between the rhombohedral (R) and MC phase fields provides the missing link for the polarization rotation path R – MB – O(orthorhombic)– MC – T (tetragonal) predicted by Vanderbilt and Cohen’s theory. © 2003 The American Physical Society.